1998
DOI: 10.1038/sj.onc.1201743
|View full text |Cite
|
Sign up to set email alerts
|

A role of the tuberous sclerosis gene-2 product during neuronal differentiation

Abstract: Tuberous sclerosis is an autosomal dominant disorder. Besides the development of benign growths (hamartomas) in di erent tissues, one hallmark of this disease is the presence of highly epileptogenic dysplastic lesions in the cerebral cortex (tubers) composed of abnormal shaped neurones. Patients often show evidence of severe mental retardation. Linkage analysis revealed two diseasedetermining genes on chromosome 9 and chromosome 16. The TSC2 gene on chromosome 16 encodes a 1784-amino acid putative tumour suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…In addition, previous studies in human neuroblastoma cell lines have demonstrated that tuberin AS-constructs reduce tuberin expression and alter cell cycle dynamics. 39 The AS-constructs did not alter cellular morphology in the NT2N, yet tuberin mRNA and protein expression was diminished by Ͼ60% and a similar reduction in tuberin expression observed in the C6 glioma cell line supported the validity of the AS-construct effects on tuberin expression. The apparently normal morphology of AS-transfected NT2N cells may have reflected the presence of enough functional tuberin to maintain cellular cytoarchitecture or may require more rigorous evaluation of subtle structural alterations.…”
Section: Neurotrophin and Tuberin Expressionmentioning
confidence: 52%
“…In addition, previous studies in human neuroblastoma cell lines have demonstrated that tuberin AS-constructs reduce tuberin expression and alter cell cycle dynamics. 39 The AS-constructs did not alter cellular morphology in the NT2N, yet tuberin mRNA and protein expression was diminished by Ͼ60% and a similar reduction in tuberin expression observed in the C6 glioma cell line supported the validity of the AS-construct effects on tuberin expression. The apparently normal morphology of AS-transfected NT2N cells may have reflected the presence of enough functional tuberin to maintain cellular cytoarchitecture or may require more rigorous evaluation of subtle structural alterations.…”
Section: Neurotrophin and Tuberin Expressionmentioning
confidence: 52%
“…6,7 Loss of tuberin expression has also been shown to lead to the cytoplasmic mislocalization and functional inactivation of the cyclindependent kinase (CDK) inhibitor p27. 7,8 While current work on TS is primarily focused on the regulation of G 1 /S phases of the tuberous sclerosis is a multi-organ disorder characterized by the formation of benign tumors, called hamartomas, which affects more than 1 million people worldwide. the syndrome is initiated by a mutation in one of two tumor suppressor genes, tSC1 or tSC2, that encode for the proteins hamartin and tuberin, respectively.…”
Section: Tuberin Regulation Of the Cell Cyclementioning
confidence: 99%
“…Hamartin stabilizes tuberin by inhibiting its interaction with the HERC1 ubiquitin ligase (Chong-Kopera et al, 2006). Tuberin has been implicated in the regulation of different cellular functions, such as endocytosis (Xiao et al, 1997), transcription (Henry et al, 1998) or neuronal differentiation (Soucek et al, 1998a). Tuberin and hamartin also regulate cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%